Model Impeachment Dalam Sistem Presidensial: Studi Komparatif Indonesia Dan Amerika Serikat - Haq, Fairuz Abdul; Sulastri, Dewi (Faculty of Law, Universitas Muhammadiyah Pontianak, 2026)
Impeachment is an important constitutional mechanism to maintain checks and balances in the presidential system. Indonesia and the United States, as countries that adopt presidentialism, have different constitutional frameworks in regulating the impeachment of presidents. This paper aims to provide a comparative analysis of the impeachment models in Indonesia and the United States. This study employs a normative juridical method with a comparative constitutional approach. The findings show that the Indonesian model emphasizes the juridical dimension through the Constitutional Court’s involvement as a legal filter, whereas the American model highlights the political aspect by granting Congress dominant authority. The Indonesian system guarantees due process of law but is procedurally complex, while the American system is simpler but vulnerable to politicization. These differences demonstrate that institutional design significantly shapes the balance of power in each country. Keywords: Impeachment, presidential system, Indonesia, United States, constitutional comparison